Forensic voice comparison using likelihood ratios based on polynomial curves fitted to the formant trajectories of Australian English /aI/ - Morrison, Geoffrey Stewart (International Journal of Speech, Language and the Law, 2009)
Earlier studies have indicated that information regarding speaker identity can be extracted from the dynamic spectral properties of diphthongs. It is widely accepted that likelihood ratios provide the logically and legally correct method for the evaluation of forensic evidence. Some studies have conducted likelihood-ratio analyses based on simple models of the dynamic formant properties of diphthongs (e.g., dual-target model), and others have used more sophisticated polynomial curve fitting models of the dynamic formant properties of diphthongs but have not conducted likelihood ratio analyses. The present study examines the strength of evidence which can be produced by a likelihood ratio analysis based on the coefficients of polynomial curves fitted to the formant trajectories of Australian English /aI/ tokens. A cubic polynomial model offers a substantial improvement over the dual-target model.